ESTIMATION OF USING MEDICATIONS OF DIFFERENT GROUPS FOR COMMUNITY-ACQUIRED PNEUMONIA TREATMENT OF PATIENTS WITH COMORBIDITIES - A.V. Demchuk (Проблеми екології та медицини)
With purpose to assess the volume and rationality of prescription of medicines for the community-acquired pneumonia (CAP) treatment in patients with chronic comorbidities a prospective study of 438 in-patients (214 men (48.9%), average age - 56,1 ± 17,9) was conducted. Chronic comorbidities were in 359 (82.0%) patients. Controlled comorbidities were in 115 (26.3%), uncontrolled - 120 (27.4%), complicated chronic diseases - 124 (28.3%). Comorbidities were absent in 79 (18.0%) patients. There were significant polypharmacy of CAP patients, mean amount of medicines was 11,0 ± 4,0. Complicated chronic diseases in patients with CAP caused prescription of 13,7 ± 5,0 drugs. CAP in-patients with uncontrolled chronic diseases received 11,0 ± 2,9 medicines. CAP in-patients with controlled comorbidities used 9,7 ± 2,7 medicines and patients without comorbidity treated with 8,4 ± 2,5 drugs (p <0.001). All patients received antibiotics, as mandatory CAP treatment. Mucolytics were prescribed 92.7%, dextrans solutions - 36.0%, which was necessary due to features of CAP course. NSAIDs were administered 48.6% patients, but half of them did not need use these medications. Using sulfocamphocaine (39.0%), thiotriazoline (25.1%) and plasmol (13.2%) did not have any positive effect at the clinical course and outcome of CAP, it was mistaken.